The Organismal Synthesis: Holistic Science and Developmental Evolution in the English-Speaking World, 1915-1954 - Esposito-Varriale, M (Springer International Publishing, 2017)
In 1915, the German physiologist Jacques Loeb published a paper titled "Mechanistic Science and Metaphysical Romance." In that article, Loeb lamented that scientific research was still infected by a "romantic" approach. Despite the triumphal achievements of the sciences based on mechanistic precepts, romantic and mystical speculations abounded. Life science, Loeb added, was besieged by mysticism, vitalism, and irrationalism. "Romantic" evolutionists indulged in unsupported theories and untested conjectures. But who were these twentiethcentury "romantics" really? In this chapter, it will be argued that, contrarily to Loeb s rhetoric, such a "romantic" community was not always constituted by irrational and mystical cranks. Rather, it was often composed of reflective scientists criticizing the overoptimism of the neo-Darwinian agenda and the unwarranted ambitions of the mechanistic (physicalist) approaches to biology. The chapter has three aims: First, to outline the main ideas of the early twentieth-century organicist agenda, with particular emphasis on evolutionary and developmental biology. Second, to briefly present the background and works of a few representative figures involved in the international community of organismal biology from the 1920s onward. Third, to show that aside from the neo-Darwinian synthesis, these scholars proposed an alternative synthesis between the 1920s and 1950s, a biological synthesis aiming to link studies on evolutionary and developmental biology within an organismal framework. The points of convergence and divergence between the two syntheses will be assessed. Then, the question of whether or not they were two incommensurable alternatives will be addressed. © Springer International Publishing AG 2017. All Rights Reserved.